Pengembangan LKPD IPS Berbasis Model Kooperatif Terpadu Membaca dan Menulis untuk Meningkatkan Literasi Siswa - Utomo, Eko Prasetyo (Jurnal Didaktika Pendidikan Dasar, 2022)
The purpose of this study was to describe the process and results of the development of IPS worksheets based on integrated cooperative reading and writing models and the effectiveness of these products in increasing literacy in social studies learning. This research is a Research and Development type with the ADDIE model which was conducted at the Bojonegoro Integrated Model Public Middle School. Product development results are tested through formative evaluation which includes validation tests of social studies material experts, expert validation tests of social studies learning media, individual, small group, and field trials. The product of the development results is in the form of social worksheets based on integrated cooperative reading and writing models. The feasibility results of the validation test by social studies material experts and social studies learning media experts are included in the very feasible category. The results of individual, small group and field trials were included in the very feasible category. The product effectiveness test results using the t-test show that the use of this product can increase student literacy. The overall results of the formative evaluation showed that the product resulting from this development is very suitable for use in social studies learning.